2021
DOI: 10.51574/jrip.v1i3.259
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Kecakapan Literasi Digital Dengan Kreativitas Mengajar Guru Dalam Kegiatan Pembelajaran

Abstract: Penelitian ini bertujuan untuk mengetahui hubungan antara kecakapan literasi digital guru dengan kreativitas mengajar guru pada Sekolah Menegah Kejuruan Negeri di Kabupaten Gowa. Penelitian ini menggunakan metode survei yang bersifat korelasi dengan pendekatan kuantitatif. Populasi dalam penelitian yaitu guru yang berstatus Pegawai Negeri Sipil yang terdapat pada 5 Sekolah Menengah Kejuruan Negeri di Kabupaten Gowa dan sebanyak 70 orang guru yang menjadi sampel melalui tekni proportional random sampling pada s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
0
0
1
Order By: Relevance
“…This is in line with research conducted by Muhammad Wadji, Tsrif kib, M Natsir, Edi Hasan, and Abidin that through digital literacy the creativity of teachers is actually increasing because the knowledge they have is not limited to the scope of the school but is comprehensive which is free to learn both online and offline. Muhammad Wadji, et al, 2021). This research is similar to the results of research from Kria Singgih Kuncoro, Sukiyanto, Muhammad Irfan, Ayu Fitri Amalia, Widowati Pusporini, Astuti Wijayanti and Sri Adir Widodo that digital literacy skills can help teachers carry out learning through internet networks (Krida Singgih Kuncoro, et al, 2022).…”
Section: Resultssupporting
confidence: 84%
“…This is in line with research conducted by Muhammad Wadji, Tsrif kib, M Natsir, Edi Hasan, and Abidin that through digital literacy the creativity of teachers is actually increasing because the knowledge they have is not limited to the scope of the school but is comprehensive which is free to learn both online and offline. Muhammad Wadji, et al, 2021). This research is similar to the results of research from Kria Singgih Kuncoro, Sukiyanto, Muhammad Irfan, Ayu Fitri Amalia, Widowati Pusporini, Astuti Wijayanti and Sri Adir Widodo that digital literacy skills can help teachers carry out learning through internet networks (Krida Singgih Kuncoro, et al, 2022).…”
Section: Resultssupporting
confidence: 84%
“…Among these findings, there is no research on the application of PjBL integrated with literacy activities, even though literacy is also an important element in answering the challenges of the 21st century. For example, one study showed that there was a positive relationship between teachers' digital literacy skills and creativity in teaching (Wajdi et al, 2021). As an effort to overcome the various problems that arise in PGMI UNSIQ students, this PjBL is collaborated with multiliteracy learning.…”
Section: Novelty Research Gap and Objectivementioning
confidence: 99%
“…Peran literasi digital bagi guru adalah untuk membantu guru mengoptimalkan penggunaan internet untuk mencari sumber-sumber informasi berkaitan dengan pembelajaran, menjadikan guru sebagai warga digital yang penuh tanggung jawab, menjadikan guru sebagai individu yang menghargai hak cipta suatu karya dengan mencantumkan sumber informasi, memudahkan guru dalam melakukan segala aktivitas digital terkait pembelajaran, meningkatkan kemampuan guru dalam mengevaluasi dan memilah sumber informasi yang sesuai dan kredibel, serta mendorong guru menciptakan hal baru sebagai bentuk pengembangan pendidikan (Levy, 2018;Anggeraini et al, 2019). Melalui penguasaan literasi digital yang baik oleh guru matematika, akan mampu mengoptimalkan penggunaan perangkat digital untuk menemukan, menyaring, dan menyalurkan kreativitas terhadap informasi pembelajaran matematika (Gilster, 1997;Nahdi & Jatisunda, 2020;Wajdi et al, 2021).…”
Section: Pendahuluanunclassified